DYNAMICS AND INTENSITY OF STRUCTURAL CHANGES IN AGRICULTURAL OUTPUT: THE CASE STUDY OF THE REPUBLIC OF SERBIA - Dimovski, Jelena; Radivojević, Vladimir; Radjenović, Tamara (Economics of Agriculture, 2023)
Agriculture as a primary sector is constantly subject to structural changes – adjustments in product features, production and consumption, technology, size of farms and agricultural holdings, manufacturing models, etc. Given the most dramatic changes occurring in the production sector, structural changes in agricultural output are precondition for understanding country’s food production and food security. Accordingly, the paper analyses the agricultural output in the Republic of Serbia in the period from 2007 to 2019. The aim of the research is to examine an intensity and dynamics of structural changes, in order to determine the most dynamic agricultural branches and period when these changes are the most intensive. The research has been conducted using Michaely Index and Lilien Index as the indicators of structural changes. Research results can be beneficiary for policy makers in developing a strategy, aiming to ensure food security and further development of key agricultural branches.